Effect of liposomal muramyl tripeptide phosphatidylethanolamine and indomethacin on hematopoietic recovery in irradiated mice - Macková, N O; Fedorocko, P (Physiological research, 2002)
The effects of liposomal muramyl tripeptide phosphatidylethanolamine (MTP-PE/MLV, radioprotective immunomodulator; 10 mg/kg) and indomethacin (INDO, inhibitor of prostaglandin production; 2 mg/kg) on post-irradiation recovery of hematopoietic functions in mice were investigated. Two agents with distinct radioprotective mechanisms were administered alone or in combination 24 h and 3 h before exposure to 7 Gy (60)Co radiation. In the post-irradiation period (3-14 days) combined pre-treatment of mice accelerated recovery of bone marrow cellularity, weight of spleen and myelopoietic and erythropoietic activity in both hematopoietic organs, compared to treatment with MTP-PE/MLV or indomethacin alone. In the peripheral blood, improved radioprotective effects of combined drug administration were found in the recovery of reticulocytes and platelet count. No further significant differences in the recovery of leukocyte count were observed in the examined groups until post-irradiation day 14. Within the first 3-6 post-irradiation days, the bone marrow and peripheral blood smears of mice pre-treated with indomethacin alone or its combination with MTP-PE/MLV more frequently featured blast cells and large cells with abundant cytoplasm which could be considered the hematopoietic stem cells.
Keywords: Animals; antiflogistika nesteroidní; Female; slezina; ženské pohlaví; Hematopoietic Stem Cells; Organ Size; Whole-Body Irradiation; Liposomes; indomethacin; imunologické faktory; počet leukocytů; Bone Marrow; Indomethacin; Mice; liposomy; myši; celotělové ozáření; Acetylmuramyl-Alanyl-Isoglutamine; Anti-Inflammatory Agents, Non-Steroidal; Hematopoiesis; Leukocyte Count; kostní dřeň; Immunologic Factors; velikost orgánu; fosfatidylethanolaminy; Radiation-Protective Agents; hematopoetické kmenové buňky; Spleen; acetylmuramyl-alanyl-isoglutamin; hematopoéza; Phosphatidylethanolamines; zvířata; radioprotektivní látky